Technostress among the Staff of College of Health Sciences Library, University of Ghana - Okine, H. (University of Ghana, 2019)
University libraries have experienced the infusion of technologies in their processes due to the advancement in technologies and also as a result of the information age that has transformed traditional methods in almost all academic libraries as well as other human institutions. The introduction of the library integrated software and OPAC has resulted in the need for library staff to be well equipped in the use of ICTs in order to remain relevant in the library profession. Hitherto librarians rendered manual services from start to finish. Currently, ICT has brought with it anxiety and the phobia for technology. This has made library work stressful. The study investigated the extent of technostress among the staff of College of Health Sciences Library, University of Ghana, causes of technostress among the professional librarians and paraprofessionals of library and the coping strategies used in an attempt to control or eliminate it, with the view to making recommendations for improved service delivery. Nineteen (19) staff members which comprised professional and paraprofessional library staff of College of Health Sciences Library were participated in the study. A semi-structured interview was used in collecting data with regards to sources of technostress. It was shown from the study that professional librarians and paraprofessionals of College of Health Sciences Library perceived challenges encountered on the job, unfavourable library environment, work overload, inadequate resources, job dissatisfaction, complex job demands, user challenges as the main causes of their technostress. Power outages and interruptions in internet connectivity were also identified to be some unique causes of technostress. Effects of technostress were identified to be unrelenting stress, heart diseases, brain damage, low job commitment, computer anxiety, as well as rigidity of workflow. In spite of the challenges related to library work, respondents were aware of benefits derived from the infusion of technologies in library processes and attested to the efficiency added to their daily routines. As such they had adopted technostress minimizing strategies such as positive thinking, resistance to prolonged sitting, meditation, isolation, sleeping, time management, watching movies and listening to music. It was also evident that staff had undergone some levels of training and had gained some form of experience on the job which helped them manage technostress. The study recommended the employment of skilled staff to support existing staff. Other recommendations are; adequate training for staff through seminars and conferences in the use of these infused technologies, the reinforcement of the counselling unit, provision of a restroom and last but not the least, the creation of a congenial environment for staff.
MPhil. Information Studies
Keywords: Information and Communication Technology (ICT); Technostress; College of Health Sciences Library; University of Ghana